The Sneaky Snow Fox - Giff, Patricia Reilly; Palmisciano, Diane (New York, 2012)
When her pet dog goes outside during a snow storm, an imaginative young girl tries to save him from the sneaky snow fox.
Keywords: Fiction; Dogs; Imagination; Snow; Fiction; Fiction